Penerapan Metode Design Thinking Pada Perancangan UI/UX Website Gereja di Gereja GMIM Nimahesaan Pinaras - Ering, Anatasya Lingkanwene; Nataliani, Yessica (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The GMIM Nimahesaan Pinaras Church has not optimally utilized information technology to support church services. Until now, all information has been limited to WhatsApp groups or reading congregational news. From these problems, a solution is provided to design and develop the UI/UX of the church website related to worship and church finances. This website's UI/UX design uses the design thinking method in five stages: Empathize, define, ideate, prototype, and test. Test results using the System Usability Scale (SUS) by assessing feasibility, convenience, and system constraints. The success of UI/UX design can be measured with a minimum score of 70%. The final results of testing with the System Usability Scale (SUS) model on the church website system produced a SUS score of 75.75% and was classified in category B, which means GOOD. Therefore, this design was successful.